2003
DOI: 10.1002/uog.940
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sonographically estimated fetal weight in 840 women with different pregnancy complications prior to induction of labor

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 14 publications
2
32
0
2
Order By: Relevance
“…Notably, EFW at the extremes of weight growth poses a problem of accuracy [4,[22][23][24] . We found that the clinical EFW method had the best ability to detect macrosomia, followed by the calculated method.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, EFW at the extremes of weight growth poses a problem of accuracy [4,[22][23][24] . We found that the clinical EFW method had the best ability to detect macrosomia, followed by the calculated method.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9][10] These formulae involve a variety of sonographically obtained biometric measurements. The sonographic estimation which is based on measurement of various fetal dimensions particularly BPD, HC, AC and FL.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Differences between ultrasound measurements of the fetus in utero and measurements of the live-born premature infant are well described (27). These differences appear to vary when there is suspected macrosomia or growth restriction (28). To date, there are no standards that reconcile high-quality ultrasound measures with neonatal anthropometric reference values in the same population.…”
Section: Hlhs Fetal Somatic Growth Trajectorymentioning
confidence: 99%